2021
DOI: 10.1007/s13202-021-01305-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica nano particles on the rheological and HTHP filtration properties of environment friendly additive in water-based drilling fluid

Abstract: Rheological and filtration properties of drilling fluid contribute a vital role in successful drilling operations. Rheological parameters such as apparent viscosity (AV), plastic viscosity (PV), yield point (YP) and gel strength of drilling fluids are very essential for hydraulic calculations and lifting of drill cuttings during the drilling operation. Control of filtration loss volume is also very important for cost effective and successful drilling operations. Therefore, the main goal of this research is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…44,45 YP represents the initial stress required to initiate the ow of non-Newtonian uids and indicates the drilling uid's effectiveness in cleaning the borehole. 46 YP is inuenced by both the volume and electrochemical attractive forces among solid particles added to the drilling uid. 47 As illustrated in Fig.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…44,45 YP represents the initial stress required to initiate the ow of non-Newtonian uids and indicates the drilling uid's effectiveness in cleaning the borehole. 46 YP is inuenced by both the volume and electrochemical attractive forces among solid particles added to the drilling uid. 47 As illustrated in Fig.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…However, variables like concentration and drilling fluid type can affect how effective nanosilica is as an addition to drilling fluid. Even though nanosilica has been shown to improve the quality of drilling fluids, more research is needed to establish the ideal concentration for various kinds of drilling fluids [62,63].…”
Section: Nanosilicamentioning
confidence: 99%
“…NPs are more reactive than their corresponding bulk materials as a result of their small particle size (1–100 nm), higher surface/volume ratio, and unstable bonds . In addition, studies have shown that most NPs (silica, titanium, and aluminum) employed in oil recovery processes are well-matched with reservoir rock minerals and, therefore, do not pose significant environmental impacts . Owing to their unique size and diffusion rate, nanoparticles can easily enter oil reservoirs and inflict changes that are intended in the specific reservoir .…”
Section: Influence Of Chemical Structures In Fluid–fluid and Fluid–ro...mentioning
confidence: 99%
“…23 In addition, studies have shown that most NPs (silica, titanium, and aluminum) employed in oil recovery processes are well-matched with reservoir rock minerals and, therefore, do not pose significant environmental impacts. 24 Owing to their unique size and diffusion rate, nanoparticles can easily enter oil reservoirs and inflict changes that are intended in the specific reservoir. 25 They can change the rheological properties of the injected fluid and fluid−fluid interaction properties, such as IFT, 26 emulsification, and thermal responses, and also alter fluid−rock interaction properties (such as wettability alteration and dissolution).…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%